Examining Student Satisfaction with Learning Management System-Based E-Learning: A Self-Determination Theory Perspective - Sari, Damar Fatika; Efendi, Agus; Sumaryati, Sri (VELES Voices of English Language Education Society, 2024)
This research aims to examine how e-learning, particularly guided by self-determination theory, impacts student satisfaction by meeting their basic needs and fostering intrinsic motivation. Specifically, we investigate various factors influencing student satisfaction, the role of e-learning, and supportive elements for e-learning satisfaction, focusing on the Indonesian context where e-learning, particularly via Learning Management Systems (LMS), is prevalent in higher education. Despite the widespread use of e-learning, there is a lack of research from the students' perspective. To address this gap, we conducted a descriptive qualitative study using the LMS SPADA platform. Through interviews and observations with 40 students, we explored their experiences with e-learning. Drawing on self-determination theory, which posits autonomy, competence, and relatedness as crucial factors in motivation and satisfaction, we assessed student satisfaction with e-learning. Our findings indicate that students generally find e-learning satisfactory, provided that certain conditions, especially those related to self-determination theory variables, are met. This research underscores the importance of adequately preparing all aspects of e-learning to enhance student satisfaction. Its implications extend to educators, students, and universities utilizing e-learning, particularly those in the Indonesian higher education sector.